LITERATURE ANALYSIS REVIEW OF THE APPLICATION OF THE CONTEXTUAL TEACHING AND LEARNING (CTL) MODEL OF SCIENCE IN ELEMENTARY SCHOOLS - Verdiana Armellia; Dela Herfiana; Ardhianti Rahayu; Nadia Pricilia. (Teaching and General Education Studies, 2025)
Many science learning activities require students to think critically, actively, and creatively. To enhance the significance of learning, educators must strive to craft engaging learning experiences for students. In the classroom teaching process, teachers not only have to use methods and strategies in delivering material but also master various learning models. Teachers often use the classical model in the learning process. Therefore, teachers need to change the learning model so that the teaching and learning process becomes more effective and meaningful. We have carried out various initiatives to improve learning outcomes and the effectiveness of science learning. One of these initiatives involves the implementation of the Contextual Teaching and Learning (CTL) learning model. The cooperative learning model aims to increase cooperation in groups and interaction between students. Therefore, research needs to conduct a more in-depth analysis to determine the extent to which cooperative learning can enhance learning outcomes and how the learning process occurs in elementary schools. This research employs qualitative methods, incorporating data collection techniques from a literature study. Overall, we highly recommend applying the CTL learning model in science subjects in elementary schools to enhance student learning outcomes.